Human alpha-globin genes demonstrate autonomous developmental regulation in transgenic mice. - Albitar, M (1991)
Recent studies have demonstrated that transcriptional activation of the human adult beta-globin transgene in mice by coinsertion of the beta-globin cluster locus control region (beta-LCR) results in loss of its adult restricted pattern of expression. Normal developmental control is reestablished by coinsertion of the fetal gamma-globin transgene in cis to the adult beta-globin gene. To test the generality of this interdependence of two globin genes for their proper developmental control, we generated transgenic mice in which the human adult alpha-globin genes are transcriptionally activated by the beta-LCR either alone or in cis to their corresponding embryonic zeta-globin gene. In both cases, the human globin transgenes were expressed at the appropriate developmental period. In contrast to the beta-globin gene, developmental control of the human adult alpha-globin transgenes appears to be autonomous and maintained even when activated by an adjacent locus control region.